Efficacy of non-wearable VR-based behavioral training for preschool children with high-functioning autism spectrum disorder: a protocol for an upcoming randomized clinical trial - Kuo, Naichi; Yao, Yukai; Ma, Chenhuan; Chu, Liting; Chen, Jinjin; Wan, Chunling; Wang, Dandan; Lu, Dingjie; Li, Xiaoqian; Wang, Yu (Frontiers in Psychiatry, 2025)
ObjectiveAutism spectrum disorder (ASD) is a neurodevelopmental condition with limited effective treatment options, including Applied Behavior Analysis, Transcranial Magnetic Stimulation, and certain medications aimed at managing associated behavioral and emotional regulation challenges. Primary interventions include educational training and behavioral modifications. However, long-term, intensive, and individualized rehabilitation training strategies are lacking, and new rehabilitation tools therefore urgently need to be developed. Virtual reality (VR) is a promising digital rehabilitation tool that may support the development of essential life skills, such as social communication and daily living abilities, in many children and adolescents with ASD. Herein, we introduce a protocol for an initial multicenter randomized controlled trial focused on preschool-aged children with ASD. This trial aims to investigate the clinical efficacy of behavioral training for young children with ASD utilizing VR technology.MethodsA total of 160 children aged 4–7 years with high-functioning ASD will be assigned to either the trial or control group in a 1:1 ratio. The trial group will undergo behavioral training based on VR technology and early family intervention guided by the rehabilitation team, whereas the control group will undergo early family intervention guided by the rehabilitation team. Both arms will undergo twice weekly sessions of either the trial or control intervention modality performed over 12 consecutive weeks. Outcome assessments will be performed at the start of the trial, throughout the intervention phase, and at follow-up intervals during the study.DiscussionThe primary aim of this trial is to determine the clinical effectiveness of cognitive training using VR technology in children with ASD.Clinical trial registrationChinese Clinical Trial Registry identifier, ChiCTR2400094189.